2017
DOI: 10.1370/afm.2102
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Assisted Treatment Should Be Part of Every Family Physician’s Practice: No

Abstract: To read or post commentaries in response to this article, see it online at http://www.AnnFamMed.org/content/15/4/309. Key words: buprenorphine, naloxone drug combination; opioid, opiate substitution therapy; opioid-related disorders; prescribing patterns, physician, primary health careSubmitted September 7, 2016; submitted, revised, March 21, 2017; accepted March 31, 2017. References 1. Lawlor J. Drug overdose deaths in Maine now averaging one a day.Portland Press Herald. November 14, 2016. T he magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…11 Buprenorphine is an alternative to methadone that can be used in primary care, 10 is an effective treatment for OUD compared with abstinence-only treatment models, 10,12,13 and is currently underused. 14,15 Limited research has shown disparities in MAT initiation in primary care settings by age, 14,16 race/ethnicity, 16 and health insurance coverage. 14,16 Findings regarding the relationships between MAT initiation and psychiatric and physical comorbidities are mixed and seem to vary depending on the specific comorbidity.…”
mentioning
confidence: 99%
“…11 Buprenorphine is an alternative to methadone that can be used in primary care, 10 is an effective treatment for OUD compared with abstinence-only treatment models, 10,12,13 and is currently underused. 14,15 Limited research has shown disparities in MAT initiation in primary care settings by age, 14,16 race/ethnicity, 16 and health insurance coverage. 14,16 Findings regarding the relationships between MAT initiation and psychiatric and physical comorbidities are mixed and seem to vary depending on the specific comorbidity.…”
mentioning
confidence: 99%
“…21,22 From our perspective, the primary barrier is the difficulty in obtaining targeted services, due to the limited availability of providers and programs, the reimbursement challenges in paying for such services, and the difficulties patients face in selecting and navigating an array of treatments. For example, one-half of addiction treatment programs do not have a prescriber.…”
mentioning
confidence: 99%
“…The research team conducted three focus groups (one per department) in January and February 2020 (prior to the onset of the COVID-19 pandemic). Focus groups were led by one of the authors (FK) and followed a semi-structured guide prepared by two of the authors (AMD, RW) based on a review of prior literature (e.g., [ 6 , 3 , 7 , 19 ], clinical expertise in treating substance use disorders (AMD, RW), and expertise in qualitative data collection and analysis (FK). The guide targeted the following domains: [ 33 ] current practices regarding the diagnosis and management of OUD, [ 25 ] familiarity and opinions regarding OUD treatment options, [ 23 ] positive and negative aspects of offering treatment for OUD in the clinic, and [ 11 ] reactions to proposed method of supporting the diagnosis of OUD and treatment of OUD with computerized clinical decision support.…”
Section: Methodsmentioning
confidence: 99%